THE EXPRESSION OF DEVOTION IN CALLIGRAPHY PAINTINGS - Harissman Harissman; Martwan Martwan (LPPMPP Institut Seni Indonesia Padangpanjang, 2019)
The forms of calligraphy paintings was expression of philosophical values of taqwa, it reflected the content of the holy Qur'an and giving the deep guidance of the importance of having attitude, behaviour and norms in a social life of human being.